2021
DOI: 10.1007/s10570-021-04273-z
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable functional finishing for cotton fabrics using chestnut shell extract

Abstract: Owing to global environmental concerns, sustainable industrial processes have become a topic of signi cant importance in various elds. Chestnut shells are byproducts of agricultural and food industries; however, they include various health-bene cial compounds such as polyphenols and avonoids. In this study, the feasibility of using chestnut shell extract as a natural functional agent for textile nishing processes was investigated. The chestnut shell extract was prepared by boiling the inner and outer shells of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A dye obtained from Keemun black tea, with theaflavins as the major polyphenol in its composition, was able to inhibit >99.9% of S. aureus in flax fabric [59]. Aqueous chestnut shell extracts, having condensed tannins and gallic and ellagic acids, were able to achieve percentage inhibitions of >99.9% against S. aureus and K. pneumoniae in cotton fabric [66,67]. Several other dyes were also able to achieve over 90% inhibition against microbes.…”
Section: Antimicrobial/antibacterialmentioning
confidence: 99%
“…A dye obtained from Keemun black tea, with theaflavins as the major polyphenol in its composition, was able to inhibit >99.9% of S. aureus in flax fabric [59]. Aqueous chestnut shell extracts, having condensed tannins and gallic and ellagic acids, were able to achieve percentage inhibitions of >99.9% against S. aureus and K. pneumoniae in cotton fabric [66,67]. Several other dyes were also able to achieve over 90% inhibition against microbes.…”
Section: Antimicrobial/antibacterialmentioning
confidence: 99%
“…Many researchers have investigated the textile dyeing and finishing potentials of coloring and functional agents extracted from different natural sources. It has been reported that bioactive compounds extracted from gallnut (Koh and Hong, 2014;Hong, 2021a), spent coffee (Koh and Hong, 2017;Hong, 2018a) and chestnut shell (Hong, 2018b(Hong, , 2021b) can be effective coloring and/or functional agents for textile treatment. However, the fabrics finished by natural compounds are known to show inferior durability in the functionality against laundry, oxidized aging, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The primary bioactive components of chestnut shell extract [13][14][15] are flavonoids and tannins. Numerous studies have delved into the potential applications of chestnut shell extract in textile dyeing [16][17][18] and its functionality, [19][20][21] although chestnut leaf extract research remains limited. According to figures from the Dandong Agricultural Bureau, the chestnut tree planting area in Dandong exceeds 1400 km 2 , with an annual output of more than 110,000 tons and a value of more than 800 million yuan.…”
mentioning
confidence: 99%